An investigation of the correlation between flavonoids and cancer - Hami, Hasan Jasim (Journal of Medical Genetics and Clinical Biology, 2024)
Antioxidant, anti-inflammatory, and anti-carcinogenic effects have been associated with flavonoids, a class of phenolic chemicals present in several plants. Brain, stomach, and blood cancers are just a few of the many types of malignancies that these substances have the potential to prevent or treat, according to research. Flavonoids have several effects on cancer, including slowing tumour development, promoting apoptosis, and preventing metastasis. Furthermore, their antioxidant capabilities can shield cells from free radical damage and lower cancer risk. To completely understand the effects of flavonoids and to define the exact quantities and methods of their administration for optimal efficacy, further study and more extensive clinical trials are needed, notwithstanding the early promising results. Nonetheless, a nutritious diet that includes foods high in flavonoids can aid in improving general health and lowering the risk of chronic illnesses